(untitled) (Research, Society and Development, 2020)
Objective: Aims to analyze the measures to cope with COVID-19 in the context of Dentistry work. Methodology: Documentary study based on news published on the Virtual Portal of the Federal and Regional Boards of Dentistry System (CFO/CRO) about the COVID-19 pandemic, between the months of March and April 2020. We used the thematic content analysis technique. In total, we analyzed 195 documents. Results: We drew up three thematic categories: i) Essential personal protective equipment during the care of the patient with COVID-19; ii) Boards defending the category during the COVID-19 pandemic and; iii) Training and recommendations about COVID-19. Conclusion: In times of the COVID-19 pandemic, during Dentistry work, we should highlight the use of personal protective equipment by professionals and patients, the support actions by the class boards (CFO/CRO) in defense of the category, besides the training on the disease, among the main coping measures. The findings reinforce the important role and participation of the CFO/CRO System in supporting professionals in this setting.